"تقييم أداء القطاع المصرفي الليبي باستخدام بطاقة الأداء المتوازن "دراسة تطبيقية على المصارف التجارية الليبية - عبدالسلام حسين البرعصي; صالح أبوبكر الجازوي; منصور محمد العشيبي (Scientific Journal of University of Benghazi, 2018)
The study aims to evaluate the performance of Libyan commercial banks from four different aspects: financial, client, learning and growth, and internal operations aspects. In terms of the financial aspect, the study relied on the financial indices extracted from aggregate financial statements of Libyan commercial in the period from 2008 to the first quarter of 2018. The client aspect, however, a questionnaire was utilized to estimate the clients' satisfaction in six Libyan commercial banks: Alwahda, Aljomhoria, Alsahari, and Altejari Alwatani, Altejara wa Altanmia, Shamal Afriquia banks. The clients of the aforementioned banks form the study population of which a sample of 473 clients was taken. For evaluation of the learning and growth aspect and internal operations of the six banks, a special questionnaire was distributed among this population that consisted of managers and their deputies, head of accounting divisions, and the internal auditors of branches of abovementioned banks. The sample taken from this population included 84 subjects. The study concluded that the commercial banks performance has both advantages and disadvantages. The advantages were represented in liquidity and capital adequacy. Meanwhile, they suffer from profitability and assets quality decline. It also found that clients were unsatisfied with the banks' performance. However, their performance in terms of supporting internal operations as well as learning and development aspects was good, The study recommends that Libyan commercial banks must adopt balance scorecard, as it is one of the modern ways of measuring and evaluating performance. Banks should also enhance the efficiency of credit divisions; support the profitability of banking sector by extending its proceeds through increasing use of Islamic investing tools. Satisfying clients through providing service characterized by high quality and reasonable price in a manner meets the clients' expectations must be at the top of their priorities.